The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1124/dmd.115.068114
|View full text |Cite
|
Sign up to set email alerts
|

Transport-Metabolism Interplay of Atazanavir in Rat Hepatocytes

Abstract: The aim of this study was to explore the mechanisms governing the intra-to extracellular unbound concentration ratio (Kp u,u ) for the HIV protease inhibitor atazanavir (ATV) in rat hepatocytes. We had previously proposed a new method to determine Kp u,u by using the unbound Km values from metabolism studies with suspended rat hepatocytes and rat liver microsomes. Following that method, we determined that the value of ATV Kp u,u was 0.32, indicating that ATV hepatocellular clearance is uptake ratelimited. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Hepatocytes in suspension are known to be across the sinusoidal membrane (Bow et al, 2008;De Bruyn et al, 2011;Keemink et al, 2015;Nicolaï, 2015). The big advantage of using suspended hepatocytes over e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes in suspension are known to be across the sinusoidal membrane (Bow et al, 2008;De Bruyn et al, 2011;Keemink et al, 2015;Nicolaï, 2015). The big advantage of using suspended hepatocytes over e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The oil‐spin method 17 was used for the hepatocyte uptake sample preparation with small modifications in rat and human hepatocytes. After the incubation, triplicate 200 μL aliquots were rapidly pipetted on top of an oil layer (82:18 silicon oil/mineral oil, 1.051 g/mL) above NaCl solution (8%, w/v) in 1.5‐mL test tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Atazanavir is a hepatic uptake transporter substrate [ 80 ], and the PBPK modeling for atazanavir did not explicitly incorporate the role of transporters for atazanavir. Importantly, Nicolai et al [ 82 ] studied the interplay of transporters and metabolism for atazanavir in rats in vitro, and found that involvement of active uptake transport did not cause high intracellular levels in this case. For atazanavir, they found that the ratio of unbound intracellular to extracellular concentration in hepatocytes was approximately 0.3, and likewise, the unbound Michaelis–Menten constant, K m,u , was >three-fold higher in hepatocytes than microsomes.…”
Section: Pbpk Modeling Of Ugt Intestinal Metabolismmentioning
confidence: 99%